In Searching Architecture and City Pattern as the Mark of Old Coastal Semarang, Indonesia - R Siti Rukayah; Muhammad Abdullah (Department of Architecture, Faculty of Engineering, Universitas Diponegoro, Indonesia., 2021)
Based on the previous research on the former of Semarang capital city, Kanjengan, there is a supposition that the area is a coastal city. As the consequence of the sedimentation process occurred by Java Island, Semarang city, and some cities in Java are no longer on the seashore. The cities that are archived in the Map of Indonesia in the 15th century and some records from foreign sailors, absolutely have several different conditions compared to the past and the present condition. How the architecture and the city’s patterns of the Old Semarang? The method of this research was conducted by exploring historical articles, toponyms, maps, and old pictures which were then compared with the remaining architecture and spatial patterns. The reading of old maps and pictures was done by using the seeing by believing approach. The analysis was performed by using the manual sketch. The architectural heritage like the former lighthouse, commercial corridors in the north of the square, and toponyms were tools to prove that the area was a seaport and a waterfront city. Old Coastal Semarang has an Architecture and urban design concept as the main gate from the sea to the city center at the time. Surrounding the main gate, they were the existence of the former lighthouse (the Menara Layur Mosque), multi-ethnics houses, toponyms indicating that some places were a former harbor, and the remaining trade corridor connecting the port and the local government center. This concept is similar to the Islamic Sultanates on the north coast of Java and the waterfront-based cities in the interior of Java. It is assumed that Semarang Old city has a similar role with the other Islamic Sultanates. This area is proper to be a city conservation area and become a part that is integrated into future urban planning.